1990
DOI: 10.1093/ajcn/51.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vitamin E and beta-carotene concentrations during radiochemotherapy preceding bone marrow transplantation

Abstract: Blood from 19 patients was examined for the essential antioxidants alpha-tocopherol and beta-carotene before, during, and after bone marrow transplantation (BMT). Marrow ablation and immunosuppression for BMT conditioning was achieved by treatment with high-dose chemotherapy, mostly combined with total body irradiation. All patients required total parenteral nutrition beginning 1 wk before BMT. After conditioning therapy the concentration of absolute and lipid-standardized alpha-tocopherol and beta-carotene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 7 publications
3
22
1
Order By: Relevance
“…Plasma MDA levels were found to be increased after high-dose therapy in these patients (1, 3, 7). In erythrocytes, SOD, glutathione peroxidase and CAT activities were reported to be decreased or increased (1,3,4,7,9). Furthermore, plasma antioxidants such as atocopherol, b-carotene and vitamin C were shown to be depleted (3,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma MDA levels were found to be increased after high-dose therapy in these patients (1, 3, 7). In erythrocytes, SOD, glutathione peroxidase and CAT activities were reported to be decreased or increased (1,3,4,7,9). Furthermore, plasma antioxidants such as atocopherol, b-carotene and vitamin C were shown to be depleted (3,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…They have severe acute and delayed toxic effects on several tissues, such as mucous membranes, gastrointestinal tract, liver, lung, bladder, central nervous system, and, rarely, other tissues possibly related to peroxidation processes and exhaustion of antioxidants. [3][4][5][6][7] It is well known that chemotherapy and radiation therapy are associated with the formation of reactive oxygen species and depletion of antioxidants, such as glutathione (GSH), antioxidant enzymes, and antioxidant vitamins such as a-tocopherol, b-carotene and vitamin C. 4,[8][9][10][11] A limited number of studies demonstrated that the conditioning therapy given to HSCT patients creates a high oxidative stress, resulting in a measured reduction in antioxidants. In summary, these studies revealed a disturbance of the pro-oxidative/antioxidative balance in the plasma of patients undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficient supply of antioxidant micronutrients of many cancer patients can also be seen in the fact that their oxidative stress markers are often increased (120,(134)(135)(136). The problem is aggravated by the falling vitamins A (137) and E (137,(138)(139)(140) blood levels under radiation therapy.…”
Section: Tumor-associated Deficit Of Micronutrients -Pathophysiologicmentioning
confidence: 99%
“…b-Carotene levels fell by 50% and vitamin E (a-tocopherol) levels by 20%. 72,73 It has long been known that both chemotherapy and radiotherapy cause malnutrition and vitamin deficiencies. 74 It seems entirely unnecessary that in the 21st century, cancer patients should still be suffering from such deprivation.…”
Section: Correcting Malnutritionmentioning
confidence: 99%